Nación/Canción - Reccitelli, Lucas (Universidad Nacional del Litoral, 2021)
This essay offers an interpretation of the ways in which the music by Liliana Herrero (1949 – present) represents the Argentinian nation. For this purpose, we initially analyze the senses of the nation which appear within this singer and philosopher’s verbal discourse, and examine them through the prism of the perspectives on the nation set out by Alejandro Grimson. Subsequently, by projecting in a metaphorical way the notion of folkmusic as metonymy of the nation over Herrero’s production, we propose the following hypothesis: by questioning, disassembling and contra–fusing («contrafusionar», a word Herrero has coined) the material of traditional folclore, Herrero questions, disassemble and brings the essentialist idea of Argentinian nation to a collision. Thus, Herrero’s production —which we periodize here— offers diverse visions about the nation within different moments. By means of the musical analysis of two of Herrero’s versions on songs of Atahualpa Yupanqui, we show the particular way in which the nation is represented within the first identified period. As an epilogue, we suggest the paths followed by the author in subsequent moments of her career.